Pengaruh Promosi dan Testimoni Pelanggan pada Social Media Instagram Terhadap Minat Beli Konsumen Kopi Kawa Jakarta Timur - Lalu Muhammad Reza Wardhana; Musthofa Hadi; Sanita Dhakirah (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
In the digital era, the development of information technology has transformed the way consumers interact with brands. Social media platforms such as Instagram have become effective tools for promotion. Kawa Kopi utilizes Instagram to market its products and attract consumer purchase intention through promotional content and customer testimonials. This study aimed to analyze the influence of promotion and testimonials on consumer purchase intention of Kawa Kopi in East Jakarta. This research was a quantitative study using an explanatory approach, with promotion, testimonial, and purchase intention as the variables. The data were collected through the distribution of questionnaires to 100 respondents in East Jakarta who had seen promotional content and testimonials on the Instagram account @kawacoffee.ind. The sampling technique used in this study was purposive sampling. The data analysis was conducted with multiple linear regression analysis and hypothesis testing. The results of the descriptive analysis showed that, on average, respondents agreed with the statements in the questionnaire. The coefficient of determination test result was 0.803 or 80.3%, indicating that the remaining 19.7% is influenced by other variables. The findings of this study indicated that both promotion and testimonials have a partial and simultaneous influence on purchase intention toward Kawa Kopi in East Jakarta. Based on the results of this study, it can be concluded that the Instagram account @kawacoffee.ind should optimize its marketing strategy, particularly in the areas of promotion and customer testimonials. Furthermore, the brand can enhance interaction with customers through the promotional and testimonial content posted on Instagram.